2022
DOI: 10.1061/(asce)mt.1943-5533.0004166
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Tensile Behavior of a High-Strength Geotextile after Exposure to Recycled Construction and Demolition Materials

Abstract: The use of recycled construction and demolition (C&D) materials as an alternative backfill in the construction of geosyntheticreinforced structures, such as embankments and retaining walls, has been pointed out as a sustainable and effective means of attenuating the environmental impacts associated with C&D waste disposal to landfill, while also reducing natural resource depletion. Creep is an important time-dependent mechanical property that must be considered when geosynthetics are used in reinforcement appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Construction and demolition (C&D) was recognised as one of the priority sectors in this Circular Economy Package due to the vast amounts of C&D wastes generated across the European Union (over 35% of total waste generation), as well as their high potential for circularity. In fact, there has been increasing evidence that C&D materials can successfully be recycled and reused in a variety of civil engineering applications, such as concrete production [ 1 , 2 ], road and railway infrastructure [ 3 , 4 , 5 , 6 ], ground improvement works [ 7 ], geosynthetic-reinforced structures [ 5 , 8 , 9 , 10 , 11 , 12 ], among others. Taking into account that the construction sector is among the main contributors to the natural resource consumption (accounting for ≈50% of all extracted materials), the incorporation of recycled materials in the construction industry could save massive amounts of natural resources and play a notable role in achieving climate neutrality.…”
Section: Introductionmentioning
confidence: 99%
“…Construction and demolition (C&D) was recognised as one of the priority sectors in this Circular Economy Package due to the vast amounts of C&D wastes generated across the European Union (over 35% of total waste generation), as well as their high potential for circularity. In fact, there has been increasing evidence that C&D materials can successfully be recycled and reused in a variety of civil engineering applications, such as concrete production [ 1 , 2 ], road and railway infrastructure [ 3 , 4 , 5 , 6 ], ground improvement works [ 7 ], geosynthetic-reinforced structures [ 5 , 8 , 9 , 10 , 11 , 12 ], among others. Taking into account that the construction sector is among the main contributors to the natural resource consumption (accounting for ≈50% of all extracted materials), the incorporation of recycled materials in the construction industry could save massive amounts of natural resources and play a notable role in achieving climate neutrality.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the enormous amounts of concrete produced, any solution that results in a small reduction in the demand for raw materials will significantly contribute to the conservation of natural resources 19,20 . For all these reasons, even replacing natural aggregates with recycled aggregates leads to conserving large amounts of natural resources 21,22 . This partial replacement provides significant environmental benefits, as it avoids landfilling and allows waste to be recycled, reduced, and reused 23,24 …”
Section: Introductionmentioning
confidence: 99%
“…19,20 For all these reasons, even replacing natural aggregates with recycled aggregates leads to conserving large amounts of natural resources. 21,22 This partial replacement provides significant environmental benefits, as it avoids landfilling and allows waste to be recycled, reduced, and reused. 23,24 The use of recycled concrete aggregates (RCA) obtained from construction and demolition wastes as aggregate in concrete has attracted great interest by researchers, and thus, efforts have been made to reduce, recycle and reuse wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Designers must also consider essential parameters for a safe and economical design, strengthening its position as a desirable alternative [13]. In the past decades, in addition to the research evaluating the environmental and economic aspects related to using RCDW materials [20][21][22][23][24][25], several studies have reported the potential substitution of natural aggregates by RCDW materials in pavement layers [6,[26][27][28][29][30][31][32][33] and backfill material for geosynthetic reinforced structures [8,12,[34][35][36][37][38][39][40][41][42]. However, Delongui et al [26] emphasized that the RCDW characteristics are valid for the research's specific application conditions (e.g., type of CDW generated, recycling process).…”
Section: Introductionmentioning
confidence: 99%